Investigating the relationship between diet quality, lifestyle and healthy eating index with severity and migraine attacks: a cross-sectional study - Feyzpour, Marziye; Sedgi, Fatemeh Maleki; Baghdadi, Ghazal; Mohammadifard, Reza; Rahimlou, Mehran (Frontiers in Nutrition, 2024)
Background: Migraine is a disabling neurovascular disorder often associated with comorbidities such as mental health disorders, cardiovascular diseases, and metabolic syndromes. While certain dietary triggers have been identified, the impact of overall diet quality on migraine severity and frequency is not well understood. This study aimed to evaluate the association between diet quality, lifestyle factors, and the Healthy Eating Index (HEI) with migraine severity and frequency.A cross-sectional study was conducted on 280 patients aged 18-50 years newly diagnosed with migraines. Dietary intake was assessed using a 147-item Food Frequency Questionnaire (FFQ), and diet quality was evaluated using the Lifelines Diet Score (LLDS) and HEI. Migraine-related disability and severity were assessed using the Migraine Disability Assessment (MIDAS) questionnaire and the Visual Analogue Scale (VAS), respectively. Logistic regression models were applied to examine the association between diet quality and migraine outcomes.Results: Higher LLDS and HEI scores were significantly associated with reduced odds of migraine-related disability. Participants in the highest LLDS tertile had an odds ratio (OR) of 0.68 (95% CI: 0.42-0.96; p = 0.02) for migraine disability. Similarly, the highest HEI tertile was associated with an OR of 0.58 (95% CI: 0.41-0.88; p = 0.025). For pain intensity, the highest tertile of LLDS showed an OR of 0.55 (95% CI: 0.38-0.75; p = 0.026), while the HEI showed an OR of 0.62 (95% CI: 0.45-0.85; p = 0.03).Higher diet quality, as measured by LLDS and HEI scores, is inversely associated with migraine severity and frequency. These findings suggest that dietary improvements may be a viable strategy for managing migraine symptoms.